(untitled) (Theatrum historiae, 2012)
The study deals with the residential strategies pursued by Count Franz Karl Swéerts-Sporck, an heir of Franz Anton Sporck, one of the most remarkable figures of the first third of the 18th century. Count Swéerts-Sporck differed from his socially highly active predecessor; he was a representative of the rural nobility, an efficient economist with good asset management as the main philosophy of life. He purposefully resigned from public career; however, he owned a great deal of land as well as a numerous and well-developed residential network of ten facilities, after completion. The study uses daily calendar records made by the Count’s Hofmeister Seeman in order to reconstruct Swéerts-Sporck’s itinerary between 1740 and 1747. These data serve to illustrate Count’s movements around his residences and the actual degrees of use of these residences. Swéerts-Sporck’s case is also confronted to the existing typical opinion of the aristocratic residential network, which, however, stems from investigations into the situation before the Battle of Bílá hora (White Mountain) and only in the highest circles of political and cultural elites. F. K. Swéerts-Sprock’s residential regime shows some stark differences not only from this widely accepted model in professional literature, but also from the residential strategy favoured by his predecessor F. A. Sporck, from whose legacy Swéerts-Sporck dissociate himself clearly.